INDAGINE SUGLI ACQUEDOTTI DI ROMA ANTICA IN AMBIENTE GIS - RAGAZZONI, CHIARA (Archeomatica, 2012)
The Ancient Aqueducts on Roman Territory - A thorough and comprehensivetreatise on the ancient aqueducts on Roman territoryhas been developed by the need to create a valid and updated interactiveconsultation tool, designed in close connection with the useof modern GIS applications and all the major computer equipment,documentation and data elements that have been largely developedin the last decade. Set up with a constant aim at usability, so it canbe appreciated by a wide range of users, the treatise retains theability to provide a high quality service from the teaching, notional,technical and scientifi c point of view.